Gut microbes modulate the effects of the flavonoid quercetin on atherosclerosis - Kazuyuki Kasahara; Robert L. Kerby; Ruben Aquino-Martinez; Abigail H. Evered; Tzu-Wen L. Cross; Jessica Everhart; Tyler K. Ulland; Colin D. Kay; Bradley W. Bolling; Fredrik Bäckhed; Federico E. Rey (npj Biofilms and Microbiomes)
Abstract Gut bacterial metabolism of dietary flavonoids results in the production of a variety of phenolic acids, whose contributions to health remain poorly understood. Here, we show that supplementation with the commonly consumed flavonoid quercetin impacted gut microbiome composition and resulted in a significant reduction in atherosclerosis burden in conventionally raised (ConvR) Apolipoprotein E (ApoE) knockout (KO) mice but not in germ-free (GF) ApoE KO mice. Metabolomic analysis revealed that consumption of quercetin significantly increased plasma levels of benzoylglutamic acid, 3,4 dihydroxybenzoic acid (3,4-DHBA) and its sulfate-conjugated form in ConvR mice, but not in GF mice supplemented with the flavonoid. Levels of these metabolites were negatively associated with atherosclerosis burden. Furthermore, we show that 3,4-DHBA prevented lipopolysaccharide (LPS)-induced decrease in transendothelial electrical resistance (TEER). These results suggest that the effects of quercetin on atherosclerosis are influenced by gut microbes and are potentially mediated by bacterial metabolites derived from the flavonoid.